Analysis of Qibla Direction Accuracy Testing Using Right-Angled Triangles by Slamet Hambali at the Musalla of IAIN Kerinci Campus from a Fiqh Perspective - Natia Rizkia; Darlius; Arzam; Khoirul Aswad (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2026)
The direction of the Qibla is very important in Islamic prayer, as errors in determining it can affect the validity of the worship. This study aims to explore the methods used in determining the Qibla direction in mosques and to evaluate their accuracy by applying the right-angled triangle method as well as fiqh analysis. This research is qualitative, employing a field research strategy that utilizes the right-angled triangle approach formulated by Slamet Hambali and fiqh. The main source used is the book *Ilmu Falak* on the determination of prayer times and Qibla directions worldwide. Data were obtained through interviews, observations, and documentation, and then analyzed through the processes of reduction, presentation, data verification, and conclusion. Research findings indicate that the qibla direction at the Prayer Room of Campus One of the State Islamic Institute of Kerinci is still determined manually, relying on the position of the sun. Meanwhile, based on astronomical calculations, the qibla direction of the Prayer Room at Campus One of the State Islamic Institute of Kerinci is at an azimuth of 295° 18' 17.3